Studi Kelayakan Tarif Commuter Line Arjonegoro Rute Sidoarjo Bojonegoro - Muhamad Alif Rifaldi; Fithri Estikhamah; Achmad Dzulfiqar Alfiansyah (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Bojonegoro Regency, Lamongan Regency, Gresik Regency, Surabaya City, and Sidoarjo Regency are areas with very high levels of community mobility. Many migrants from Bojonegoro and Lamongan travel to Surabaya for work and further education. One of the transportation options available is the Arjonegoro Commuter Line. This study aims to determine passenger satisfaction with the appropriateness of fares based on their ability and willingness to pay. Primary data collection was obtained by distributing questionnaires to passengers. The Ability to Pay (ATP) analysis obtained a value of Rp 10,034 and analysis using the Willingness to Pay (WTP) method obtained a value of Rp 3,539. This condition indicates that the ability to pay is greater than the willingness to pay. This indicates that the current fare can be said to be appropriate because the fare is between the ATP and WTP values.